O cuidado à saúde mental na primeira infância nos centros de atenção psicossocial infantojuvenis (CAPSij) - Silva, Giovana Siaticosqui Barbedo da (Universidade Federal de São Carlos, 2022)
The present study aims to understand more about mental health care in early childhood in Centros de Atenção Psicossocial infantojuvenil (CAPSij). In addition, the specific objectives are: to identify what are the existing care actions/strategies for this population and to describe the professionals' perception of the care offered. To this end, an exploratory descriptive study with a quantitative and qualitative approach was developed, carried out with five professionals linked to two CAPSij in a large city in the state of São Paulo. Two instruments were used for data collection: a CAPSij characterization form and an online questionnaire. Quantitative data were entered and processed using Excel® spreadsheets and presented descriptively. For discursive questions, Bardin's categorical analysis technique was used. The results point to an increase in the prevalence of children aged 0 to 6 years in CAPSij, the main demand being developmental delay, such as autism spectrum disorder (ASD). The CAPSij is pointed out as an important equipment for the care and support of the family and stimulation of development, from the perspective of psychosocial care. In addition, the challenges are related to the difficulty with intersectoral work and the limited availability of resources. More investments and studies in this field are considered important, aiming to understand how mental health care in early childhood has been proposed and developed, since the literature points to many debates and challenges that permeate care for this public
Mental health care in the first childhood in care centers psychosocial children and youth (CAPSij)
Keywords: Saúde Mental; Criança; Serviços de Saúde Mental; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL